Tomorrow's professor preparing for academic careers in science and engineering - Reis, Richard M. (IEEE Press, 1997)
Tomorrow's Professor is designed to help you prepare for, find, and succeed at academic careers in science and engineering. It looks at the full range of North American four-year academic institutions while featuring 30 vignettes and more than 50 individual stories that bring to life the principles and strategies outlined in the book.